Stalking and Other Forms of Dating Violence: Lessons Learned from You in Relation to Cyber Safety - Chugh, Ritesh (Journal of interpersonal violence, 2022)
Often, individuals share private information on social media, being unaware of online dangers. You, a popular psychological thriller series on Netflix, raises issues of stalking behaviors through social media as part of a pattern of dating violence. Using a qualitative content analysis approach, this study examined how social media is used for erotic stalking, dating violence, and cyber safety awareness (or lack thereof) in You. The researchers analyzed all 10 episodes of the first season of You independently, taking notes. A combined in-depth analysis included discussions of messages and meanings resulting in three overarching themes: obsessive online and in-person erotic stalking, controlling behaviors in the context of the dating relationship, and an apparent indifference about cyber safety with oversharing of personal information on social media, which was exploited by the lead protagonist. You raises important concerns including inappropriate dating behaviors such as stalking, coercive control, violence, and questionable masculine attitudes, which are interwoven with an apparent lack of knowledge and understanding in relation to cyber safety. We concluded that raising awareness of the importance of online safety and security in the context of a dating relationship is imperative and that You can be used as an educational tool.